2002
DOI: 10.1097/00004770-200210000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hydroxyl Ions from Gutta-Percha Points with Calcium Hydroxide in Their Composition: An In Vivo Study

Abstract: The aim of this study was to quantify variations in the pH of calcium-hydroxide, gutta-percha cones that had remained for 1 week inside the root canals of molars or premolars whose endodontic treatment could not be concluded in a single visit. All teeth were instrumented and dried before the placement of the points. The cones were removed, and placed in vials with distilled water. Additional, new gutta-percha cones were also studied as a control. The pH was measured by a pH meter, model CRISON MicropH 2001. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Azabal-Arroyo et al ., evaluated antimicrobial activity of materials containing Ca(OH) 2 in solid media presents some difficulties as there is low solubility of the Ca(OH) 2 in solid medium. [14] This fact could explain the results obtained in this study that show that the Gutta-percha points containing Ca(OH) 2 did not present antimicrobial activity on tested strains. Further long term studies need to be done to confirm the same.…”
Section: Discussionmentioning
confidence: 74%
“…Azabal-Arroyo et al ., evaluated antimicrobial activity of materials containing Ca(OH) 2 in solid media presents some difficulties as there is low solubility of the Ca(OH) 2 in solid medium. [14] This fact could explain the results obtained in this study that show that the Gutta-percha points containing Ca(OH) 2 did not present antimicrobial activity on tested strains. Further long term studies need to be done to confirm the same.…”
Section: Discussionmentioning
confidence: 74%
“…[25] The calcium hydroxide containing gutta-percha points showed a significantly lower alkalizing potential than Ca (OH) 2 mixed with distilled water. Calt et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported maximum pH values of 9.5 and 10.9, respectively. [21] Calt et al . showed that calcium hydroxide gutta-percha points did not induce any changes in pH and calcium ion levels.…”
Section: Discussionmentioning
confidence: 99%